Analisis Determinan Kualitas Sumber Daya Manusia di Indonesia - Yusraini Harahap; Melti Roza Adry (Universitas Negeri Padang, 2020)
This study aims to determine the effect of energy consumption, environmental quality, economic growth on the human development index, partially and simultanneously.This type of research used in this research is descriptive and associative research. The data in this study are secondary data in the form of time series from 1987 to 2017, with documentation data collection techniques and literature studies obtained from relevant agencies. The methods used in this study are Multiple Linear Berganda, Clasical Assumption Test.The results of this study indicate that energy consumption has positive and significant effect on the human development index in Indonesia, enviromental quality has a positive and significant effect on the human development index in Indonesia, economic growth has a negative and significant effect on the human development index in Indonesia, and energy consumption, enviromental quality, and economic growth have a significant effect on the human development index in Indonesia.